Adaptation of the patient suffering from diabetes mellitus type II to the disease and to the treatment - Júnia Marise da Silva Rocha; Thereza Maria Magalhães Moreira; Dafne Paiva Rodrigues (Rev Rene)
The study aimed at understanding the patient suffering from diabetes type II’s adaptation to the disease and to the treatment. This qualitative study has been carried out with people suffering from the disease whose knowledge of the diagnosis took place at least one year ago. The discussion on the data was based on Roy’s Model and described adaptive and ineffective responses from patients, associated to incentives in the types of self-concept/group identity, physical-physiologic features, interdependence and role playing. The valorization of personal and family participation in the treatment of diabetes should be inserted in nursing care in order to promote adaptive responses.